Associations between Inflammatory Cytokine Gene Polymorphisms and Susceptibilities to Intracranial Aneurysm in Chinese Population. (16th January 2021) - Xu, Lu; Hu, Liming; Hu, Chongyu; Liu, Junyu; Li, Bingyang; Liao, Xin; Zhou, Jilin; Liu, Songlin; Li, Yifeng; Yuan, Dun; Jiang, Weixi; Yan, Junxia
Abstract : Intracranial aneurysm (IA) is a complex disease caused by genetic and environmental factors. Evidence indicates that inflammation plays an important role in IA occurrence. We aimed to explore the associations between inflammatory cytokine gene polymorphisms and IA in a Chinese population. This study enrolled 768 participants of Han ethnicity, including 384 patients with IA and 384 healthy individuals. Sixteen single nucleotide polymorphisms (SNPs) of IL1, IL6, IL12, and TNF-α genes were genotyped using the Sequenom MassARRAY platform. Univariate and multivariate logistic regression analyses were used to analyze the associations. We found IL12B rs3181216 was significantly associated with IA in the recessive and additive models (OR = 0.46, 95% CI = 0.23–0.89, P = 0.022 ; OR = 0.74, 95% CI = 0.56–0.98, P = 0.034, respectively). TNF-α rs1799964 was associated with IA in dominant and additive models (OR = 0.67, 95% CI = 0.46–0.98, P = 0.041 ; OR = 0.71, 95% CI = 0.51–0.98, P = 0.034, respectively). IL1A rs17561 was associated with single IA susceptibility (dominant model: OR = 0.52, 95% CI = 0.31–0.85, P = 0.040 ). The IL12B rs3181216 polymorphism was associated with single IA susceptibility in the recessive model (OR = 0.41, 95% CI = 0.18–0.93, P = 0.033 ). The IL12B rs2195940 polymorphism was associated with multiple IAs susceptibility (dominant model: OR = 0.28, 95% CI = 0.09–0.89, P = 0.031 ; additive model: OR = 0.28, 95% CI = 0.09–0.90, P = 0.032 ). TNF-α rs1799964 was associated with multiple IAs susceptibility in the dominant model (OR = 0.54, 95% CI = 0.30–0.97, P = 0.040 ). No associations were found between other polymorphisms and IA susceptibility. Therefore, IL1A, IL12B, and TNF-α gene polymorphisms are associated with IA susceptibility in a Chinese population.